KELAYAKAN MEDIA FLIPBOOK PADA SUBMATERI TUMBUHAN PAKU (Pteridophyta) KELAS X SMA - Sahira, Aini; Syamswisna, Syamswisna; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The aims of this study were to measure the feasibility of the flipbook  as the learning media sub of the fern (Pteridophyta) materials of senior high school class X. The form of the study with descriptive method. Validation sheet was used as the intrument of research. The flipbook media was examined by two lecturers of biologic education study program of FKIP Untan and three of biology teachers of class X in three different school in sebawi district and the surrounding. Based on the assessment of validators, the flipbook  was valid with the average score Content Validity Index (CVI) 0,88 and feasible as the learning media sub of the fern (Pteridophyta) materials. Key words: Feasibility, flipbook, ferns.